2015/16 I‐MOVE/I‐MOVE+ multicentre case‐control study in Europe: Moderate vaccine effectiveness estimates against influenza A(H1N1)pdm09 and low estimates against lineage‐mismatched influenza B among children. Issue 4 (14th March 2018) - Kissling, Esther; Valenciano, Marta; Pozo, Francisco; Vilcu, Ana‐Maria; Reuss, Annicka; Rizzo, Caterina; Larrauri, Amparo; Horváth, Judit Krisztina; Brytting, Mia; Domegan, Lisa; Korczyńska, Monika; Meijer, Adam; et al.
Abstract : Background: During the 2015/16 influenza season in Europe, the cocirculating influenza viruses were A(H1N1)pdm09 and B/Victoria, which was antigenically distinct from the B/Yamagata component in the trivalent influenza vaccine. Methods: We used the test‐negative design in a multicentre case‐control study in twelve European countries to measure 2015/16 influenza vaccine effectiveness (VE) against medically attended influenza‐like illness (ILI) laboratory‐confirmed as influenza. General practitioners swabbed a systematic sample of consulting ILI patients and a random sample of influenza‐positive swabs was sequenced. We calculated adjusted VE against influenza A(H1N1)pdm09, A(H1N1)pdm09 genetic group 6B.1 and influenza B overall and by age group. Results: We included 11 430 ILI patients, of which 2272 were influenza A(H1N1)pdm09 and 2901 were influenza B cases. Overall VE against influenza A(H1N1)pdm09 was 32.9% (95% CI: 15.5‐46.7). Among those aged 0‐14, 15‐64 and ≥65 years, VE against A(H1N1)pdm09 was 31.9% (95% CI:− 32.3 to 65.0), 41.4% (95% CI: 20.5‐56.7) and 13.2% (95% CI:− 38.0 to 45.3), respectively. Overall VE against influenza A(H1N1)pdm09 genetic group 6B.1 was 32.8% (95% CI:− 4.1 to 56.7). Among those aged 0‐14, 15‐64 and ≥65 years, VE against influenza B was− 47.6% (95% CI:− 124.9 to 3.1), 27.3% (95% CI:− 4.6 to 49.4) and 9.3% (95% CI:− 44.1 to 42.9), respectively. Conclusions: Vaccine effectiveness (VE) against influenza A(H1N1)pdm09 and its genetic group 6B.1 was moderate in children and adults, and low among individuals ≥65 years. Vaccine effectiveness (VE) against influenza B was low and heterogeneous among age groups. More information on effects of previous vaccination and previous infection is needed to understand the VE results against influenza B in the context of a mismatched vaccine.